FOODAlyzer usability: Advances in food safety education - Wen-Li Seow; Kai Wei Lee; Roshariza Haris; Umi Kalsom Md Ariffin; Shing Wei Ng; Sook Yee Lim; Madihah Mohd Saudi; Abdul Rahman Mohamad Gobil; Nurul Azmawati Mohamed; Nor Afiah Mohd Zulkefli; Tengku Zetty Maztura Tengku Jamaluddin; Noris Mohd Norowi; et al. (PLoS ONE, 2025)
The proliferation of digital technologies offers innovative avenues for public health education. This study evaluates the usability of FOODAlyzer © , a web-based application designed to enhance food safety awareness among Generation Z university students in Peninsular Malaysia. Using a mixed-methods approach, researchers collected data from 419 Gen Z students via online questionnaires. The study comprehensively assessed the app’s effectiveness in improving knowledge, attitudes, and risk perception regarding food poisoning prevention. The results demonstrated significant positive outcomes. Majority of respondents (94.8%) acknowledged FOODAlyzer© utility in selecting quality food premises. The app demonstrated strong performance across key usability metrics, with participants reporting high levels of interactivity, accessibility, and ease of learning. Notably, 89.7% of respondents expressed intentions to utilize the app before ordering food, and 90.6% would recommend it to others. While the app demonstrated strong potential, user feedback revealed critical areas for improvement, which were categorized into two main themes: Technical enhancements and food safety education advancements. Key findings highlighted five technical improvement themes. Users called for greater accessibility and inclusivity, including multilingual support, a dedicated mobile app, and features accommodating diverse age groups. Suggestions for interface design focused on improving icon clarity, tooltip implementation, and visual readability. To boost engagement, users recommended an interactive experience with embedded multimedia, peer review systems, and instant feedback mechanisms. Enhancements in functionality, such as a more reliable system and streamlined login process, were also prioritized. Finally, users proposed interconnectedness with external services and government platforms to extend its reach and credibility. Regarding food safety education, three key themes emerge. Users suggested enhancing educational content with clearer criteria to educate both consumers and premise owners. Incorporating reward-based motivation through gamification, quizzes, and promotional incentives was recommended to encourage consistent use. Finally, users emphasized the need for clearer evaluation tools, advocating for simplified question formats, intuitive scales and reduced questionnaire length to minimize user fatigue and improve accuracy. This research provides a user-centered roadmap for developing effective digital public health tools. By addressing these identified limitations and incorporating stakeholder feedback, FOODAlyzer © can be optimized to better serve as a model for future digital interventions aimed at improving food safety practices among young adults and the broader community.